2001
DOI: 10.1159/000055777
|View full text |Cite
|
Sign up to set email alerts
|

Lacrimal Gland Abscess: An Unusual Complication of Rhinosinusitis

Abstract: We report the case of a 72-year-old female suffering from mild myelodysplasia who initially presented with a peri-orbital cellulitis secondary to rhinosinusitis. The pre-septal infection failed to completely resolve despite intensive antibiotic therapy and endoscopic drainage of the sinuses. Computerised tomography revealed a complicating suppuration of the lacrimal gland. Incision and drainage of the lacrimal gland abscess led to a complete resolution of the pre-septal cellulitis. Suppuration of the lacrimal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 1 publication
0
18
0
1
Order By: Relevance
“…[217][218][219][220][221] Sinus disease is the underlying cause of about 10% of intracranial suppuration, 222,223 and is associated with 10% to 90% of periorbital infections. 224 In large epidemiological studies, the overall incidence of complications ranged from 3 per million individuals per year in the Netherlands, 225 to 2.7 to 4.3 per million children per year in the United States (intracranial), 226 to 2.5 per million of population per year in France.…”
Section: Ve Ars: Complicationsmentioning
confidence: 99%
“…[217][218][219][220][221] Sinus disease is the underlying cause of about 10% of intracranial suppuration, 222,223 and is associated with 10% to 90% of periorbital infections. 224 In large epidemiological studies, the overall incidence of complications ranged from 3 per million individuals per year in the Netherlands, 225 to 2.7 to 4.3 per million children per year in the United States (intracranial), 226 to 2.5 per million of population per year in France.…”
Section: Ve Ars: Complicationsmentioning
confidence: 99%
“…Periorbital cellulitis can be complicated by serious sequelae, including: visual loss from ischaemic retinopathy and optic neuropathy 12 (due to increased intraorbital pressure); restricted ocular movements; and spread of infection locally and centrally leading to cavernous sinus thrombosis, 13 Periorbital cellulitis complicated by lacrimal gland abscess is rare, with only six cases reported in the literature, of which only two were paediatric cases. 3,4,[16][17][18] In our case, the diagnosis was confirmed on contrast-enhanced CT, after the patient had ongoing, marked periorbital swelling and pain which failed to respond to antibiotics. As we experienced in this case, an abscess can be easily overlooked on an unenhanced CT scan, and this radiological investigation should always be performed with contrast for this reason.…”
Section: Discussionmentioning
confidence: 76%
“…ASBD has been reported in patients ranging in age from 1 year8 to 72 years6 (mean age 24 years) in Australia,7 America,4 12 18 Pakistan,10 India,19 Malaysia,3 Canada13 and the UK 1 5 6. While Mathias and colleagues8 acknowledge that their series of MRSA orbital cellulitis reflects the severe end of the disease spectrum, they found that all patients with ASBD were from the paediatric subgroup (younger than 18 years), and within the paediatric group of patients included in that study 83% had ASBD.…”
Section: Discussionmentioning
confidence: 99%
“…Contiguous spread from overlying cutaneous infection has been suggested in the presence of preceding stye and boils 1 10. Pre-existing anatomical abnormalities, such as cysts or ductule stones,11 12 may supply a nidus for infection, and the dacryoadenitis may be associated with rhinosinusitis 5 6 10. One patient in the current series may have had underlying sarcoidosis but was lost to follow-up.…”
Section: Discussionmentioning
confidence: 99%